2019
DOI: 10.31661/jbpe.v0i0.937
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Tinnitus Detection based on Brain Network Analysis of EEG Functional Connectivity

Abstract: Background:Tinnitus known as a central nervous system disorder is correlated with specific oscillatory activities within auditory and non-auditory brain areas. Several studies in the past few years have revealed that in the most tinnitus cases, the response pattern of neurons in auditory system is changed due to auditory deafferentation, which leads to variation and disruption of the brain networks.Objective: In this paper, we introduce an approach to automatically distinguish tinnitus individuals from healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
10
0
2
Order By: Relevance
“…Then, with a moving window and a peak-to-peak threshold all parts, which exceeded ±100 μv were removed. The preprocessed data, containing the least amount of artifacts, was segmented into 5-second trials (24 trials, totally 120 sec) which were in the range of other resting-state EEG studies [21, 2830].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, with a moving window and a peak-to-peak threshold all parts, which exceeded ±100 μv were removed. The preprocessed data, containing the least amount of artifacts, was segmented into 5-second trials (24 trials, totally 120 sec) which were in the range of other resting-state EEG studies [21, 2830].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that the small-world topology abnormally alters in many disease e.g. major depressive disorder[17], Parkinson's disease [18], Alzheimer’s disease [19], schizophrenia and tinnitus [20, 21], opioids (heroin) and methamphetamine abuse [13, 22], Cirrhosis [23], cognitive disorders related to aging [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…BP, ECG, and EEG along with many other objective physiological, or psychological, function tests can be undertaken in the field, in ecologically valid settings ( 91 , 92 ). Although there is no single physiological objective measure of tinnitus itself, years of lab based search has identified many related markers of tinnitus related activity, for example neural networks associated with tinnitus ( 93 ), measures of emotion, and stress ( 94 ). New miniaturized wearable technology is now available to make longitudinal measures of physiological function ( 95 104 ) that can be related to behavioral indices of tinnitus.…”
Section: Resultsmentioning
confidence: 99%
“…The auditory network with tinnitus has a comparatively different level of segregation and integration in most rhythm bands (Mohagheghian et al 2019). The connectivity in the superior frontal cortex has various degrees of reduction for all frequency bands during the development stage of tinnitus (Lan et al 2020).…”
Section: Discussion and Future Challengesmentioning
confidence: 99%